Ceftriaxone-resistant Salmonella enterica serovar Newport: a case report from South India - Sumana, Mahadevaiah Neelambike; Maheshwarappa, Yogeesh D.; Rao, Morubagal Raghavendra; Deepashree, R.; Karthik, M. V. S. Krishna; Shah, Nikita K. (Frontiers in Public Health, 2024)
Salmonella enterica serovar Newport is a human pathogen underreported in developing countries. This case report reported Salmonella enterica serovar Newport, which causes bacteremia and acute gastroenteritis. The patient had a recent history of antibiotic consumption, which is a significant risk factor for acquiring multidrug-resistant serovar Newport. This is the first case report of Salmonella enterica serovar Newport resistant to ceftriaxone. Surveillance of infections caused by nontyphoidal Salmonella is of utmost importance because delayed identification, serotyping, and susceptibility testing may delay the administration of antibiotics, leading to worsening outcomes.